Psychological Stressors and Psychological Recovery Among University Students During and After Psychological Distress (Covid-19 as a Model) - Fuaad Mohammed FREH; Muhand Mohammed Abdulsattar AlNuaimy; Noor Wadah Satea (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: Psychological studies have indicated high prevalence rates of stress resulting from life stressors, especially during and after the pandemic of Covid-19. None of these studies, however have addressed the nature of the psychological stressors and recovery among Iraqis. This study aimed to address this gab in literature by investigating the prevalence of the indicators for the psychological stressors and recovery. The study also aimed to identify the nature of the relationship between psychological stressors and recovery during and after the conditions of psychological distress among a sample of Iraqi students. Methodology: Five-hundred and forty-four students (225 male and 319 female) were randomly selected from to participate in this study. The short-version (23 items) of Recovery-Stress Questionnaire by Kallus (2011) was adopted. The questionnaire was translated into Arabic language. Validity of translation and other psychometric properties were extracted. Results: After analyzing the data, the results showed that 16.24% had a high degree of psychological stressors and recovery, while 15.7% showed a low degree. The results also indicated that 15.8% of the participants had high-level psychological stressors compared to 13.36% who had a low degree of suffering from stress. Too, 22.38% had a high rate of recovery, compared to 14.62% who had a low rate of recovery from psychological stressors. The results also indicated that there is a statistically significant correlation between psychological stressors and recovery, and that (0.577) of stress can predict psychological stressors and recovery. Conclusions: The clinical and research implications of the findings are discussed..